BUDAYA PINGIT DALAM TARI “PEREMPUAN DALAM BATAS” - Prasika Dwi Nugra; Susas Rita Loravianti; Syaiful Erman (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT “Perempuan Dalam Batas” Dance is an imaginative expression of anxiety about the condition of women in Indonesia. This dance work is inspired by the interpretation of seclusion cultural phenomenon in Palembang, South Sumatera called pingit. Women in the time of Sultanate of Palembang Darussalam were secluded and equipped with skill to weave in order to acquire a partner/couple of the nobility later on. Women during the colonial era were secluded in pangkeng hidden from the invaders. Pingit is a form of protection arranged by the women’s parents with a specific purpose at different times. That protective imaginary space then becomes the starting point of this work creation by focusing on women as the object of seclusion and impact occurred from the presence of the space. Fundamentally, the idea of protection in seclusion is to protect the women nevertheless, the way of doing the protection results on negative effects toward the women themselves. The negative effects of seclusion ultimately result on limited movement/expression and social space for women in their life. Method of creation applied in this work was observation (exploration of data, interview, and documentation), data analysis, creation process (contemplation, exploration of movement, formation), preparation, performance, and evaluation. This work is divided into 4 (four) parts namely 1) The interpretation of women in seclusion during the era of Palembang Darussalam Sultanate and the era of colonization; 2) The interpretation of seclusion as the cause of women’s limited movement and social space; 3) The interpretation of the uprising as the response of secluded women; 4) The interpretation of women who are unable to get off of the seclusion issue. Keywords: Pingit culture, Women, Choreography.